Morning commute problem with supply management considering parking and ride-sourcing - Su, Qida (2021)
Managing morning commute traffic through parking provision management has been well studied in the literature. One conventional assumption made in most previous studies is that all commuters require parking spaces at CBD area. However, in recent years, due to technological advancements and low market entry barrier, more and more e-dispatch FHVs (eFHVs) are provided in service. The rapidly growing eFHVs, on one hand, supply substantial trip services and complete the trips requiring no parking demand; on the other hand, imposes congestion effects on all commuters. In this study, we investigate the morning commute problem with bottleneck congestion and parking space constraints in the presence of ride-sourcing service. The within-day dynamic equilibrium and its travel pattern are examined. Meanwhile, we explore the optimal supply of parking spaces and ride-sourcing services to best manage the commute traffic. To minimize system total travel costs, the optimal quantity control of parking spaces and eFHVs is determined, which indeed addresses a critical issue on how to regulate the supply of eFHVs.